(untitled) (Terr@ Plural, 2023)
Roadside tree planting is sometimes neglected by many Brazilian city councils, as they do not consider trees as part of urban infrastructure. So, this paper aims to analyze the planning of street tree planting in the city of Maringá, located in the Northern State of Paraná. The specific objectives were (i) to identify municipal legislations regarding urban tree planting from 1950 to 2022; and (ii) to analyze the 2020 Maringá Urban Tree Management Plan (PGAU). It analyzed the urban occupation and street tree planting history, as well as the PGAU, by means of bibliographical and documental research. Maringá initially had its tree planting planning carried out by the Companhia de Melhoramentos Norte do Paraná between 1947 and 1982, and later by the Municipal Government, which published its PGAU only in the year 2020. It is concluded that the PGAU is an important planning management document developed by this municipality, but it has some deficiencies that could be further improved.